The ancestral cascades arc: Cenozoic evolution of the central Sierra Nevada (California) and the birth of the new plate boundary - Busby,CJ; Hagan,JC; Putirka,K; Pluhar,CJ; Gans,PB; Wagner,DL; Rood,D; DeOreo,SB; Skilling,I (Special Paper of the Geological Society of America, 2008)
We integrate new stratigraphic, structural, geochemical, geochronological, and magnetostratigraphic data on Cenozoic volcanic rocks in the central Sierra Nevada to arrive at closely inter-related new models for: (1) the paleogeography of the ancestral Cascades arc, (2) the stratigraphic record of uplift events in the Sierra Nevada, (3) the tectonic controls on volcanic styles and compositions in the arc, and (4) the birth of a new plate margin. Previous workers have assumed that the ancestral Cascades arc consisted of stratovolcanoes, similar to the modern Cascades arc, but we suggest that the arc was composed largely of numerous, very small centers, where magmas frequently leaked up strands of the Sierran frontal fault zone. These small centers erupted to produce andesite lava domes that collapsed to produce block-and-ash flows, which were reworked into paleocanyons as volcanic debris flows and streamflow deposits. Where intrusions rose up through water-saturated paleocanyon fill, they formed peperite complexes that were commonly destabilized to form debris flows. Paleocanyons that were cut into Cretaceous bedrock and filled with Oligocene to late Miocene strata not only provide a stratigraphic record of the ancestral Cascades arc volcanism, but also deep unconformities within them record tectonic events. Preliminary correlation of newly mapped unconformities and new geochronological, magnetostratigraphic, and structural data allow us to propose three episodes of Cenozoic uplift that may correspond to (1) early Miocene onset of arc magmatism (ca. 15 Ma), (2) middle Miocene onset of Basin and Range faulting (ca. 10 Ma), and (3) late Miocene arrival of the triple junction (ca. 6 Ma), perhaps coinciding with a second episode of rapid extension on the range front. Oligocene ignimbrites, which erupted from calderas in central Nevada and filled Sierran paleocanyons, were deeply eroded during the early Miocene uplift event. The middle Miocene event is recorded by growth f